SCSO: A novel sine-cosine based swarm optimization algorithm for numerical function optimization - Tuncer, Türker (International University of Sarajevo, 2018)
Many swarm optimization algorithms have been presented in the literature and these algorithms are generally nature-inspired algorithms. In this paper a novel sine-cosine based particle swarm optimization (SCSO) is presented. In SCSO, firstly particles are generated randomly in the search space. Personal best value and velocity of the particles are calculated and by using sine, cosine and difference valuee. Calculated velocity is used for updating particles. The proposed algorithm is basic algorithm and approximately 30 rows MATLAB codes are used to implement the proposed algorithm. This short code surprisingly has high optimization capability. In order to evaluate performance and prove success of this algorithm, 14 well known numerical functions was used and the results illustrate that the proposed algorithm is successful in numerical functions optimization. © 2018 International University of Sarajevo.
Keywords: Numerical Functions Optimization; Sine-cosine optimization Swarm Optimization; Swarm inspired evolutionary algorithm